Student Perceptions of an Interprofessional Collaboration in an Experiential Learning Setting. Issue 1 (4th May 2022) - Spicer, Briana J.; Burk, Brooke N.; Mahowald, Megan
Abstract: Interprofessional collaboration (IPC) in an experiential learning setting can provide undergraduate and graduate students opportunities to learn about other professional practices, address patient/individual needs, and learn to work in a team setting that is respective of many disciplines. The current study examined the impact of an interprofessional summer camp, Camp Maverick: Rec N' Read, on undergraduate and graduate students' perceptions of their learning. The students participated in focus groups after the IPC experience to reflect on their learning throughout the camp. Our findings suggest that a camp setting, outside of clinical practice, can provide a unique learning experience for individuals in a variety of disciplines related to health, especially those in recreation and leisure sciences. We conclude that the additional IPC learning experiences are needed to bring students the opportunity to learn professional practices in clinical sciences, humanities, and education. It will better prepare students for professional practice.